2019
DOI: 10.1016/j.humov.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Does transcranial direct current stimulation during writing alleviate upper limb freezing in people with Parkinson’s disease? A pilot study

Abstract: Transcranial direct current stimulation (tDCS) over the primary motor cortex (M1) can boost motor performance in Parkinson's disease (PD) when it is applied at rest. However, the potential supplementary therapeutic effect of the concurrent application of tDCS during the training of motor tasks is largely unknown. The present study examined the effects of tDCS on upper limb motor blocks during a freezing-provoking writing task (the funnel task) requiring up- and down-stroke movements at alternating amplitudes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…Seven studies had cross-over design [25,28,34,37,[39][40][41] and ten were controlled trials with parallel arms. Three studies did not mention information regarding how or if experiments were blinded [37,40,42], three studies consisted of single-blind experiments [28,34,36] and eleven studies consisted of double-blind experiments. It is worth mentioning that all the included studies randomly assigned participants into groups/conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies had cross-over design [25,28,34,37,[39][40][41] and ten were controlled trials with parallel arms. Three studies did not mention information regarding how or if experiments were blinded [37,40,42], three studies consisted of single-blind experiments [28,34,36] and eleven studies consisted of double-blind experiments. It is worth mentioning that all the included studies randomly assigned participants into groups/conditions.…”
Section: Methodsmentioning
confidence: 99%
“…[25] and cognitive training [26,27]. The idea is that such combinations would promote greater, synergistic effects than the interventions applied separately [28,29]. In this context, tDCS can be applied concurrently or as a priming technique.…”
Section: Introductionmentioning
confidence: 99%
“…Nitsche & Paulus, 2000). This predictability has led to recent investigation into tDCS application in pathological population including Parkinson's disease (Broeder et al, 2019;Bueno et al, 2019), epilepsy (Lin et al, 2018;Tecchio et al, 2018) stroke rehabilitation (Biou et al, 2019;Solomons & Shanmugasundaram, 2019), cerebral palsy (Inguaggiato et al, 2019), chronic pain (Callai et al, 2019;Jafarzadeh et al, 2019), depression (Aparicio et al, 2019) and cognitive impairment (Emonson et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation to SMA (2 mA, 13 min) (Costa-Ribeiro et al, 2016) or DLPFC (10 sessions, 2 mA, 20 min) (Doruk et al, 2014) revealed no significant benefit. Broeder et al (2019) noted an increase in writing amplitude with anodal tDCS to M1 (1 mA, 20 min). Fregni et al (2006) also noted some benefit in Purdue pegboard task with anodal tDCS to M1 (1 mA, 20 min), but other studies found no significant benefit in dexterity tasks with single-or multi-session tDCS to the fronto-polar area (five sessions, 1 mA, 15 min) (Ishikuro et al, 2018) or DLPFC (10 sessions, 2 mA, 20 min) (Doruk et al, 2014).…”
Section: (B) Effect On Upper Limb Motor Functionmentioning
confidence: 95%
“…• Gait and balance (Benninger et al, 2010;Verheyden et al, 2013;Capecci et al, 2014;Kaski et al, 2014a;Mak and Yu, 2014;Manenti et al, 2014;Valentino et al, 2014;Costa-Ribeiro et al, 2016Schabrun et al, 2016;Swank et al, 2016;Fernandez-Lago et al, 2017;Lattari et al, 2017;Criminger et al, 2018;da Silva et al, 2018;Dagan et al, 2018;Harris et al, 2018;Yotnuengnit et al, 2018;Alizad et al, 2019;Putzolu et al, 2019) • Upper limb function (Fregni et al, 2006;Benninger et al, 2010;Doruk et al, 2014;Salimpour et al, 2015;Costa-Ribeiro et al, 2016;Ferrucci et al, 2016;Schabrun et al, 2016;Cosentino et al, 2017;Ishikuro et al, 2018;Broeder et al, 2019) • Cognition (Nitsche et al, 2005;Boggio et al, 2006;Biundo et al, 2015;Manenti et al, 2016;Elder et al, 2017;Lawrence et al, 2018;Adenzato et al, 2019) • Impulsive pathological gambling behavior (Benussi et al, 2017a) • Speech (Pereira et al, 2013) • Sleep (Hadoush et al, 2018) • Fatigue …”
Section: Mode Of Tesmentioning
confidence: 99%